Mesenchymal stem cells for osteoarthritis: Recent advances in related cell therapy - Jianjing Lin; Jingtao Huang; Zilu Jiao; Mengyuan Nian; Canfeng Li; Yali Dai; Shicheng Jia; Xintao Zhang (Bioengineering & Translational Medicine)
Abstract Osteoarthritis (OA) is a degenerative joint disease that affects the entire joint and has been a huge burden on the health care system worldwide. Although traditional therapy and targeted cartilage cell therapy have made significant progress in the treatment of OA and cartilage regeneration, there are still many problems. Mesenchymal stem cells from various tissues are the most studied cell type and have been used in preclinical and clinical studies of OA, because they are more widely available, have a greater capacity for in vitro expansion, and have anti‐inflammatory and immunomodulatory properties compared to autologous chondrocytes. This article will systematically review the latest developments in these areas. It may provide new insights for improving OA and cartilage regeneration.